Excertos orquestrais do repertório sinfônico brasileiro para viola: proposições para o estudo e aprendizado da técnica do instrumento - Rodrigo Santana de Souza (2023)
Orchestral excerpts are the main evaluation tool in selection processes for national and international orchestras. However, in these auditions, Brazilian orchestral music is not contemplated. There are few records in the curriculum of music schools, conservatories and universities, where the practice of studying orchestral excerpts from Brazilian symphonic repertoires is unobfuscated and studied. In this context, excerpts from Brazilian symphonic music have the same technical and interpretative difficulties as orchestral excerpts in traditional use. This research analyzes to what extent an extraction of orchestral excerpts from the Brazilian symphonic repertoire contributes to the learning and technical knowledge of the violist, through a selection of Brazilian repertoires. The research also proposes to encourage the inclusion of this material in auditions for positions of musicians in Brazilian orchestras and as a technical complement to the daily study of the violist in formation. The approach used is qualitative bibliographical and quantitative.